A comparison study on ornament of Rumoh Aceh in Aceh Besar and Umah Pitu Ruang in Aceh Tengah / Zulhadi Sahputra and Muhammad Heru Arie Edytia - Sahputra, Zulhadi; Arie Edytia, Muhammad Heru (Universiti Teknologi MARA, Perak, 2021)
This study aims to describe the diversity of ornaments used in traditional house in Aceh Besar and Aceh Tengah. The diversity of ornaments was viewed through four approaches, including: the location of ornament used in traditional house, types of ornament, the basic form of geometric, and the function. The location of ornaments used in traditional houses Is divided into three parts, lower part (the feet of the building), middle part (the body of the building), and top (the head of the building). The type of ornament described the category of ornament. The basic form of ornament is a study that described the geometric type of ornament. Finally, the ornament function is to explain the aesthetic, meaning, and technical functions of using ornamentation. Rumoh Aceh and Umah Pitu Ruang are cultural assets and local identities of Aceh with all its local wisdom. This study was conducted as an effort to preserve the existence of ornaments in Aceh traditional house, especially in Aceh Besar and Aceh Tengah.